Antifungal susceptibility profile of Candida spp. causing candidemia in an Indonesian tertiary hospital - Andini Wulandari; Rebriarina Hapsari; Mujahidah; Desvita Sari; Iva Puspitasari; Dodik Tugasworo Pramukarso (Journal of Clinical Microbiology and Infectious Diseases, 2021)
Introduction: Invasive candidiasis has emerged as a significant public health problem in recent years, and candidemia is the most common form. Identification of the Candida species is important since some Candida species showed an increasing trend of resistance to commonly used antifungal agents. This study was conducted to describe primary demographic data and the distribution of Candida species along with their antifungal susceptibility profiles among patients with candidemia. Methods: We conducted a retrospective descriptive study on patients with candidemia and their Candida species identification and antifungal susceptibility testing (ID&AST) results at Dr. Kariadi Hospital, Indonesia, from January 2017 to December 2020. Identification and antifungal susceptibility testing of Candida species during these 4 years were determined using the Vitek-2 system. After collecting the data, it was analyzed by using SPSS 25.sav. The data was analyzed distributively, and was presented by table and barchart. Result: A total of 85 Candida species were isolated from 74 patients. Infant age (58.10%) and intensive care (64.86%) patients contributed to most of the candidemia cases. The three most common Candida species isolated during the study period were C. parapsilosis (36.9%), C. tropicalis (25%), and C. albicans (25%). Among all Candida isolates, 98.9% were susceptible to Fluconazole and Voriconazole, 99% were susceptible to Caspofungin, Micafungin, and Flucytosine, 95.7 % were susceptible to Amphotericin B. Echinocandin resistance emerged in 2020 from a C. glabrata isolate. Conclusion: The present study, conducted in a tertiary care Indonesian hospital, showed the predominance of non-albicans Candida with favorable antifungal susceptibility profiles.